Cobalt(II), copper(II), nickel(II), and Zinc(II) complexes of naphthaldehyde thiazolyl hydrazones - Yilmaz, I; Çukurovali, A (Polish Chemical Soc, 2004)
Two new Schiff base ligands containing 2,4-disubstituted thiazoles and cyclobutane rings, 2-hydroxy-1-naphthaldehyde [4-(3-methyl-3-mesitylcyclobutyl)-1,3-thiazol-2-yl] hydrazone ((LH)-H-1) and 1-(2-hydroxy-1-naphthyl)etanone [4-(3-methyl-3-mesitylcyclobutyl)-1,3-thiazol-2-yl] hydrazone ((LH)-H-2) and their mononuclear complexes with a 1:2 metal: ligand ratio have been prepared from chloride salts of Co(II), Cu(II),Ni(II)and Zn(II) in EtOH. The authenticity of new ligands and their complexes have been established by elemental analyses, infrared, H-1 and C-13 NMR spectra, and by magnetic susceptibility measurements. Thermal properties of the ligands and complexes have been studied by thermogravimetric analysis (TGA) technique. The novel complexes of transition metal ions contain two monoanionic, bidentate NO ligands. It was found that all the complexes are mononuclear.
Keywords: 2,4-disubstituted thiazole; Schiff base; cyclobutane; hydrazone; complexes